Employee Reactions to Leader-Initiated Crisis Preparation: Core Dimensions - Selart, Marcus 1963-; Johansen, Svein Tvedt; Nesse, Synnøve (2013)
Crisis prevention plans are usually evaluated based on their effects in terms of preventing or limiting organizational crisis. In this survey-based study, the focus was instead on how such plans influence employees’ reactions in terms of risk perception and well-being. Five different organizations were addressed in the study. Hypothesis 1 tested the assumption that leadership crisis preparation would lead to lower perceived risk among the employees. Hypothesis 2 tested the conjecture that it would also lead to a higher degree of well-being. Both hypotheses were supported. The results and their implications are discussed.
Keywords: Well-being; Risk perception; Employee Relations; Crisis Management; Human Resource Management; Leadership